KAJIAN TERHADAP RASM DALAM NASKAH MUSHAF AL-QUR`AN MADURA - Luluk Asfiatur Rohmah (STAI AL-ANWAR SARANG, 2018)
Muslim’s approach to the holy book al-Qur ʻan is expressed in various activities, reading, memorizing, writing, transcribing, and others. The copying of Al-Qur ʻan has been being strictly controlled by the rasm used, rasm uthmani and rasm imla'i, and the copies has been being maintained by the museum, pesantren, collectors, heirs and others with various purposes and interests. This paper examines the manuscripts of the Mushaf al-Qur ʻan H. Habibullah from Konang Village, Bangkalan, Madura from the aspect of using rasm, vowels and punctuation. The result of this study is that the copying of the manuscripts of the Mushaf al-Qurʻan H. Habibullah is inconsistent in applying the rules for writing rasm uthmānī and rasm imlā'i from the rules for discarding letters, adding letters, writing hamzah, changing letters and writing punctuation (harakat). The writing of this Mushaf manuscript also came out of the corridors of the rules for writing rasm uthmānī and rasm imlā'i. This inconsistency was influenced by the absence of a reference basis for writing the Mushaf at that time, as well as the unfamiliarity of Nusantara Muslims with the Arabic language rules, nahw-ṣarf.